Perancangan Switch Manageable Untuk Pengelolaan Virtual LAN Menggunakan Linux CentOS Pada SMKN 2 Kuripan - Mohammad Taufan Asri Zaen; Syahadatul Intihan (Jurnal Informatika dan Rekayasa Elektronik, 2018)
In realizing an integrated service both internally and externally, SMK Negeri 2 Kuripan need a reliable computer network infrastructure and can connect all units in a single integrated network. Current state of computer networks in SMK Negeri 2 Kuripan is still a large computer networks and complex. With the computer network conditions like this, it causes traffic in computer networks become dense eventually cause some problems such as access to an application to be slow. Under these conditions, then the computer network in SMK Negeri 2 Kuripan requires a segmentation of the network / subnetwork according to the needs of the organization. Computer networks in SMK Negeri 2 Kuripan is still using a single network ID, so as to make the segmentation of networks of smaller needed a way to break the single Network ID into a Network ID. Subnetting is a way to break up the Network ID is by using hostid bits to form part subnetID. Subnetting process is done on a single Network ID is produced 11 subnet that has been established based on the needs of organizations SMK Negeri 2 Kuripan. Utilization of Virtual LAN topologies for the physical design and subnetting for logic design is able to provide optimization of the performance of computer networks. Optimization is achieved due to the use of VLAN network can reduce the collision data (collision) by blocking packets / frames that do not need to be outstanding in the network. In addition, VLANs can also be split in / out broadcast domain, so that data packets sent from a host will only be forwarded to the destination host and other hosts will not accept packets / frames.